1998
DOI: 10.1111/j.1469-7998.1998.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of density and weather on survival of bighorn sheep lambs (Ovis canadensis)

Abstract: Density-dependence in juvenile survival may be dif®cult to detect if survival is also affected by densityindependent factors. We investigated the relationships among weather parameters, population density, and lamb survival of bighorn sheep with long-term data from a marked population where we manipulated population density. We distinguished neonatal survival and winter survival. Density interacted with weather variables to affect neonatal survival; spring and winter temperatures had a positive effect on neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 46 publications
(95 reference statements)
6
126
2
1
Order By: Relevance
“…Winter is generally considered the energetic bottleneck for white-tailed deer at northern latitudes (Mautz 1978;Potvin et al 1981;Dumont et al 2000) and browse surveys (Lock 1997) suggest that the winter carrying-capacity for deer in Nova Scotia is low relative to other areas in northeastern North America (Potvin and Huot 1983;Lock 1997;Dumont et al 2000). Further, carrying capacity decreases precipitously with increasing snow cover (Potvin and Huot 1983) suggesting that there could be a significant interaction between density and climate in limiting deer population growth, as previously documented for red deer on Rum (Cervus elaphus; Benton et al 1995), bighorn sheep in western Canada (Ovis canadensis Shaw; Portier et al 1998) and Soay sheep on St. Kilda Island (Ovis aries L.; Grenfell et al 1998). However, we could detect no interaction between climate and density.…”
Section: Figmentioning
confidence: 74%
See 1 more Smart Citation
“…Winter is generally considered the energetic bottleneck for white-tailed deer at northern latitudes (Mautz 1978;Potvin et al 1981;Dumont et al 2000) and browse surveys (Lock 1997) suggest that the winter carrying-capacity for deer in Nova Scotia is low relative to other areas in northeastern North America (Potvin and Huot 1983;Lock 1997;Dumont et al 2000). Further, carrying capacity decreases precipitously with increasing snow cover (Potvin and Huot 1983) suggesting that there could be a significant interaction between density and climate in limiting deer population growth, as previously documented for red deer on Rum (Cervus elaphus; Benton et al 1995), bighorn sheep in western Canada (Ovis canadensis Shaw; Portier et al 1998) and Soay sheep on St. Kilda Island (Ovis aries L.; Grenfell et al 1998). However, we could detect no interaction between climate and density.…”
Section: Figmentioning
confidence: 74%
“…Climate fluctuations (Forchhammer et al 1998;Stenseth 1998, 1999;Milner et al 1999;Aanes et al 2000), density-dependent forage competition (Messier 1991(Messier , 1995Benton et al 1995;Gaillard et al 1998;Portier et al 1998), harvest (Fuller 1990;Langvatn and Loison 1999;Solberg et al 1999), and predation (Messier 1991(Messier , 1994Post and Stenseth 1998;Ballard et al 1999) have all been shown to significantly affect population growth of ungulate species at northern latitudes. However, the relative contributions of, and potential interactions among, these factors continue to spark debate.…”
Section: Introductionmentioning
confidence: 96%
“…The following fixed independent variables were included in the models: "calf sex", NAO winter index (NAO t ) and density. Because the effect of climatic factors may be density-dependent (Gaillard et al 1996;Portier et al 1998;Forchhammer et al 2001;Weladji and Holand 2003) and is expected to be sex-specific (Clutton-Brock et al 1985;CluttonBrock and Coulson 2002) in polygynous and sexually dimorphic ungulates, interactions between NAO t and both density and calf sex were included in all models. In addition to these two interaction terms, all other interactions were tested but are not reported unless significant.…”
Section: Data Analysesmentioning
confidence: 99%
“…At high densities in confined areas, populations of large mammals exhibit reductions in fecundity and juvenile survival (Eberhardt 1977, Clutton-Brock et al 1987, Portier et al 1988, Gaillard et al 2000, which result from self-regulating processes that are density--dependent Taper 1994, Foley 1994). In our study and others (Sabo et al 2004), comparisons of simple diffusion methods for estimating population viability using density--dependent models revealed that density--independent methods underestimate maximum growth rate and overestimate the variance compared to the results of the Ricker model.…”
Section: Discussionmentioning
confidence: 99%